2010
DOI: 10.1002/app.33194
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion removal properties of crosslinked poly(acrylamide‐co‐2‐acrylamide‐2‐methyl‐1‐propane sulfonic acid)

Abstract: Poly(acrylamide-co-2-acrylamide-2-methyl-1-propane sulfonic acid) P(AAm-co-APSA) copolymers have been prepared to be used in the extraction of Pb(II), Hg(II), Cd(II), Zn(II), Al(III), and Cr(III) metal ions from aqueous solution by a batch and column equilibration procedures. The adsorption capacity was increased with pH for all metal ions studied. The contact time and the temperature did not affect the retention significantly. The resin did not show a preference in a mixture of Pb(II), Cd(II), Zn(II), and Cr(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The composites showed high adsorption capacities at pH values of 3 and 5 and the addition of montmorillonite did not result in a significant enhanced adsorption capacity [21]. Rivas et al [17] studied the metal ion removal properties of crosslinked poly(acrylamide-co-2-acrylamide-2-methyl-1-propane sulfonic acid) for the extraction of Pb(II), Hg(II), Cd(II), Zn(II), Al(III), and Cr(III) metal ions from aqueous solution, they found that the adsorption capacity was increased with the pH. Rivas et al also studied the synthesis and removal properties of poly(N-hydroxymethyl acrylamide-co-acrylic acid) and poly(Nhydroxymethyl acrylamide-co-acrylamidoglycolic acid).…”
Section: Introductionmentioning
confidence: 96%
“…The composites showed high adsorption capacities at pH values of 3 and 5 and the addition of montmorillonite did not result in a significant enhanced adsorption capacity [21]. Rivas et al [17] studied the metal ion removal properties of crosslinked poly(acrylamide-co-2-acrylamide-2-methyl-1-propane sulfonic acid) for the extraction of Pb(II), Hg(II), Cd(II), Zn(II), Al(III), and Cr(III) metal ions from aqueous solution, they found that the adsorption capacity was increased with the pH. Rivas et al also studied the synthesis and removal properties of poly(N-hydroxymethyl acrylamide-co-acrylic acid) and poly(Nhydroxymethyl acrylamide-co-acrylamidoglycolic acid).…”
Section: Introductionmentioning
confidence: 96%
“…Substituting the variables in Eq. (4) one gets (5) and integrating Eq. (5) for the following boundary conditions: t=0 tot = t, andq = and q = 0 and q = qe, one obtains the final form 6A plot of versus gives the value of the constants (g/mg min), from which it is possible to calculate (mg/g).…”
Section: Column Adsorptionmentioning
confidence: 99%
“…Cavus et al studied competitive heavy metal removal by poly(2-acrylamido-2-methyl-1-propane sulfonic acid-co-itaconic acid) to remove Pb(II), Cu(II), and Cd(II) ions from aqueous solutions with great retention [3].Urbano et al studied the sorption properties of composites based on 2-acrylamido-2-methyl-1-propane sulfonic acid for Pb(II), Cu(II), and Cd(II). The addition of montmorillonite enhanced the mechanical properties of the ion exchange resin [4].Rivas et al studied the metal ion removal properties of crosslinked poly(acrylamide-co-2-acrylamide-2-methyl-1-propane sulfonic acid) for the extraction of Pb(II), Hg(II), Cd(II), Zn(II), Al(III), and Cr(III) metal ions from aqueous solution; they found that the adsorption capacity increased with pH [5]. Rivas et al studied the retention of Cu(II), Cd(II), Co(II), Hg(II), Ni(II), Zn(II), Cr(III), and Ag(I) by poly(2acrylamido-2-methyl-1-propanesulfonic acid), poly(methacrylic acid), and poly[(2-acrylamido-2-methyl-1-propanesulfonic acid)-co-(methacrylic acid)] by the Liquid-phase Polymer-based Retention (LPR) technique [6].Bajaj et al synthesized and characterized different copolymers of acrylonitrile-acrylic acids [7].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of Cu(II), Cd(II), Co(II), Hg(II), Ni(II), Zn(II), Cr(III) and Ag(I) ions by polymers such as poly(2-acrylamido-2-methyl-1-propane-sulfonic acid), poly(methacrylic acid), poly(2-acrylamido-2-methyl-1-propane-sulfonic acid-co-methacrylic acid), and cross-linked copolymer poly(4-styrene sodium sulfonate-co-acrylic acid) was investigated. [7][8] Recent studies by this research team include the synthesis of cation-exchange resins based on water-soluble copolymers: poly(acrylamide-co-styrene sodium sulfonate), poly(2-acrylamido-2-methyl-1-propanesulfonic acid-co-acrylic acid), poly(2-acrylamidoglycolic acid-co-2-acrylamido-2-methyl-1-propanesulfonic ac- [9][10][11] The developed ion-exchange copolymers demonstrated the ability to remove Cr(III) ions from aqueous solutions. Synthetic polymer materials for ion exchange adsorbents consisting of 4-styrene sodium sulfonate, methacrylic acid and methyl methacrylate at different ratios were prepared by polymerization in solution.…”
Section: Introductionmentioning
confidence: 99%